Transcranial direct current stimulation and its effect on cognitive symptoms of schizophrenia: An updated review - Sadia Rehman Safwi; Abid Rizvi; Mohammad Amir Usmani; Karrar Husain; Kanwarjeet Brar; Deep Yadava (Schizophrenia Research: Cognition)
Objective: Cognitive impairments in schizophrenia significantly affect functional outcomes and quality of life. This meta-analysis evaluates the effectiveness of transcranial direct current stimulation (tDCS) as an intervention for cognitive deficits in individuals with schizophrenia. Methods: From May 20 to June 15, 2024, a systematic search of PubMed, Medline, Embase, and the Cochrane central register of controlled trials was conducted. After applying eligibility criteria, 13 randomized sham-controlled trials were included, involving 261 participants in the tDCS group and 247 in the sham group. Standardized mean difference (SMD) was computed to measure the effect size of cognitive outcomes. Statistical analyses were performed using a random-effects model to account for heterogeneity. Results: The pooled analysis yielded an SMD of 0.09 (95 % CI: −0.17 to 0.35), indicating a non-significant difference between tDCS and sham on cognitive outcomes. Moderate heterogeneity (I2 = 44 %) was observed, attributed to variations in tDCS protocols, participant demographics, and cognitive assessment tools. Although certain studies showed improvements in specific domains like working memory, the overall impact of tDCS on cognitive symptoms was not statistically significant. Conclusions: This meta-analysis underscores the lack of significant evidence for tDCS in improving cognitive deficits in schizophrenia. The findings highlight the urgent need for standardizing tDCS protocols and employing domain-specific cognitive assessments. This standardization, along with the collection of more domain-specific data, is crucial for future research and the improvement of current methodologies.